1984
DOI: 10.1523/jneurosci.04-03-00627.1984
|View full text |Cite
|
Sign up to set email alerts
|

Localization of phencyclidine binding sites on alpha and beta subunits of the nicotinic acetylcholine receptor from Torpedo ocellata electric organ using azido phencyclidine

Abstract: A photolabile derivative of phencycliding (PCP), azido phencyclidine (AZ-PCP), was synthesized and used to localize PCP binding sites on the acetylcholine receptor from Torpedo ocellata electric organ. In the dark, the binding of micromolar concentrations of [3H]AZ-PCP to a receptor-enriched membrane preparation fits a single dissociation constant (& = 2.65 PM) and is very similar to the binding of ["HIPCP. The agonist carbamylcholine increases the association rate (and the affinity) of these ligands to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In attempts to locate the binding sites for noncompetitive inhibitors, several groups have photoaffinity-labeled Torpedo receptors efficiently with azido or mustard derivatives of noncompetitive inhibitors (Oswald & Changeux, 1981a; Kaldany & Karlin, 1983;Haring et al, 1984) or weakly by UV irradiation of the unmodified inhibitors (Oswald & Changeux, 1981b;Heidmann et al, 1983). Different inhibitors label different subunits, although the ability of chlorpromazine to label all four subunits with roughly equal efficiency and the displacement of chlorpromazine by other inhibitors suggest that the binding site for the inhibitors may exist in an area that is accessible to all receptor subunits, possibly in or near the central hydrophilic crevice, where the distances to all five receptor subunits are minimal (Changeux et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…In attempts to locate the binding sites for noncompetitive inhibitors, several groups have photoaffinity-labeled Torpedo receptors efficiently with azido or mustard derivatives of noncompetitive inhibitors (Oswald & Changeux, 1981a; Kaldany & Karlin, 1983;Haring et al, 1984) or weakly by UV irradiation of the unmodified inhibitors (Oswald & Changeux, 1981b;Heidmann et al, 1983). Different inhibitors label different subunits, although the ability of chlorpromazine to label all four subunits with roughly equal efficiency and the displacement of chlorpromazine by other inhibitors suggest that the binding site for the inhibitors may exist in an area that is accessible to all receptor subunits, possibly in or near the central hydrophilic crevice, where the distances to all five receptor subunits are minimal (Changeux et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Although the sensitivity of labeling to various pharmacological active drugs was not reported, these authors indicated that several polypeptides were labeled by [3H]AZ-PCP, in agreement with the results reported here. In this connection, it should be noted that photoaffinity labeling of other receptors (e.g., nicotinic cholinergic receptors or opioid receptors) have also yielded labeling of multiple bands (Oswald & Changeux, 1981;Haring et al, 1983aHaring et al, , 1984Bidlack et al, 1981), which in the case of the nicotinic receptors are constituents of the receptor molecule. Interestingly, polypeptides with molecular weights similar to those labeled by [3H]AZ-PCP were also identified by affinity labeling or affinity chromatography of opioid receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we describe the binding characteristics and affinity labeling of rat hippocampal PCP receptors, determined by employing the photoactivatable analogue of PCP N-[ 1 -(3-azidophenyl)cyclohexyl]piperidine (azidophencyclidine, AZ-PCP). This drug was used in our previous studies to localize the site of noncompetitive blockers of cholinergic receptors from Torpedo electric organ (Haring et al, 1983a(Haring et al, , 1984.…”
mentioning
confidence: 99%
“…Both 3H-labeled perhydrohistrionicotoxin and phencyclidine, under ultraviolet irradiation (107), gave similar results. However, with T. californica and quinacrine mustard (36,109) [or triphenylmethylphosphonium (110)] or with T. ocellata and azidophencyclidine (111), labeling occurred primarily at level of the a or the ,3 chains, respectively. With T. marmorata, 3H-labeled chlorpromazine labeled all four chains, suggesting that they all contribute to the single highaffinity site present per oligomer (104,107).…”
Section: Morphology Of the Receptor Proteinmentioning
confidence: 99%